2008
DOI: 10.1186/1471-2156-9-81
|View full text |Cite
|
Sign up to set email alerts
|

SNP discovery in swine by reduced representation and high throughput pyrosequencing

Abstract: Background: Relatively little information is available for sequence variation in the pig. We previously used a combination of short read (25 base pair) high-throughput sequencing and reduced genomic representation to discover > 60,000 single nucleotide polymorphisms (SNP) in cattle, but the current lack of complete genome sequence limits this approach in swine. Longer-read pyrosequencing-based technologies have the potential to overcome this limitation by providing sufficient flanking sequence information for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 14 publications
2
84
2
2
Order By: Relevance
“…Likewise, we found a strong correspondence between the predicted allele frequencies based on the pooled samples and those obtained from Sanger sequencing of a different sample of crickets. This result is similar to those reported in other SNP discovery experiments with comparable coverage (Van Tassell et al 2008;Wiedmann et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, we found a strong correspondence between the predicted allele frequencies based on the pooled samples and those obtained from Sanger sequencing of a different sample of crickets. This result is similar to those reported in other SNP discovery experiments with comparable coverage (Van Tassell et al 2008;Wiedmann et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Wiedmann et al (2008) reported that the SNP density in pigs was higher than 1:370 bp. Here the SNP frequency of the pDRD2 gene is one per 80 bp, similar to previous results before correction for sample size (Jungerius et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One of the first drastic changes comes from the ease with which a large number of markers are now produced, either as by-products of completed or ongoing genome sequencing projects or generated using parallel sequencing technologies and reduced representation libraries aimed at producing SNP [Van Tassell et al, 2008;Wiedmann et al, 2008]. These markers are genotyped by using the new genotyping technologies that were developed for SNP.…”
Section: Rh Mapping Todaymentioning
confidence: 99%